IDENTIFIKASI BAKTERI PENGHASIL PENISILIN G ASILASE DARI BEBERAPA SUNGAI DI KOTA PADANG - Julyada, Romi; Siregar, Megahati; Fitriani, Vivi (STKIP PGRI Sumbar, 2013)
ABSTRACT Penicillin G acylase is an enzime that catalyzes the hidrolysis of penicillin G acylase into 6-aminopenisilanat acid (6-APA). 6-APA is a basic ingredient inthe manufacture of semisynthetic penicillin. Acylase penicillin G can be by produced of microorganisms, such as fungi penisillium and various types of bacteria, such as Bacillus, Escherichia coli. Acylase penicillin G producing bakteria have been isolated from saveral rivers in the Padang city, but the identification has not been done. Associated with it to identify bacteria producing penicillin G acylase of saveral rivers in the Padang city. This research aims to determine the type of bacteria producing penicillin G acylase of saveral rivers in the Padang city. This research was conducted in July 2013 laboratory Kopertis Region X and in August 2013 in the Balai Penyidikan and Pengujian Veteriner Regional II Bukit Tinggi. Identification is carried out morphological and biochemical. The research uses desckriptive method. Results of bacterial identification by morphological and biochemical which shown that the bacteria producing penicillin G acylase of saveral rivers in the Padang city is a bacterium of the genus Bacillus.